2019
DOI: 10.1111/mcn.12794
|View full text |Cite
|
Sign up to set email alerts
|

Integrated school based nutrition programme improved the knowledge of mother and schoolchildren

Abstract: This study evaluates the effects of nutrition education on improving knowledge, attitude, and practice (KAP) of mothers and the improvement of the nutritional status of their children. A cluster randomized controlled design using multistage sampling was employed. The integrated school‐based nutrition programme included gardening, nutrition education for parents, and supplementary feeding for children (GarNESup). KAP of mothers was assessed using pretested questionnaires administered by teachers. The randomly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 9 publications
0
27
0
2
Order By: Relevance
“…Thirteen of 14 studies reported improved knowledge of ≥1 topic related to nutrition, WASH, or health, with diverse effects. All studies reporting outcomes on knowledge of vitamin A ( 37 , 44 ), maternal nutrition ( 45 ), general nutrition ( 36, 44, 46–49 ), and health and nutrition-related diseases ( 44, 45, 49, 50 ) reported improvements. At least half of the studies looking at children's knowledge of nutrition (1 of 2) ( 51 ), and WASH (3/4) ( 42, 49, 51 ) documented improvements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen of 14 studies reported improved knowledge of ≥1 topic related to nutrition, WASH, or health, with diverse effects. All studies reporting outcomes on knowledge of vitamin A ( 37 , 44 ), maternal nutrition ( 45 ), general nutrition ( 36, 44, 46–49 ), and health and nutrition-related diseases ( 44, 45, 49, 50 ) reported improvements. At least half of the studies looking at children's knowledge of nutrition (1 of 2) ( 51 ), and WASH (3/4) ( 42, 49, 51 ) documented improvements.…”
Section: Resultsmentioning
confidence: 99%
“…Three of 4 studies looking at the effect on income/selling showed improvements in food items, such as vegetables (2 of 3) ( 39, 40 ), OFSP ( 36 ), as well as a nonfood item (cottonseed) ( 39 ). Three studies reported changes in mothers’ attitudes on meal preparation, mothers’ ability to convince their children to eat vegetables (1 of 1) ( 49 ), and children's probability of consuming vegetables and fruits (2 of 2) ( 51 , 53 ). Four studies also reported improvement in ≥1 domain of women's empowerment.…”
Section: Resultsmentioning
confidence: 99%
“…Gardening programs are flexible in all shapes and sizes fit with the needs and resources of every school (Alderson et al, 2015). The International Institute for Rural Reconstruction describe that it is needed some features to promote school garden resilience: school garden must use organic fertilizer, must have at least 200-m 2 garden bed and deep dug at least 1 ft, good water source, proper drainage system, and use mulch to protect soil (Angeles-Agdeppa, Monville-Oro, Gonsalves, & Capanzana, 2019;De Vlieger, Riley, Miller, Collins, & Bucher, 2018). Running a school garden requires some knowledge, people skills, and common sense that related with how to plan and manage, find resources, collaborate and motivate with those involved, and organize garden work and lessons (FAO, 2009;Sherman, 2010).…”
Section: 6mentioning
confidence: 99%
“…The authors of the five papers demonstrate how a range of nutrition‐sensitive interventions, including home gardens and enhanced homestead food production, cropping improvements and diversification, and food fortification can be scaled up to contribute to the improvement of diets and nutritional outcomes in women and children. The papers provide evidence from efficacy (Michaux et al, ) and effectiveness (Angeles‐Agdeppa, Monville‐Oro, Gonsalves, & Capanzana, ) studies, to assessments of technologies to optimise value‐added processing (Durairaj, Gurumurthy, Nachimuthu, Muniappan, & Balasubramanian, ) and cost effectiveness of interventions (Walters, Ndau, Saleh, Mosha, & Horton, ), to a report of bringing a proven intervention to scale (Diosady, Mannar, & Krishnaswamy, ). These interventions aim to improve nutrition through a number of direct and indirect pathways, outlined in a simplified programme impact pathway adapted from Masset, Haddad, Cornelius, and Isaza‐Castro (; Figure ).…”
Section: Summary Of Select Nutrition‐sensitive Cifsrf Projectsmentioning
confidence: 99%
“…Second, Angeles‐Agdeppa et al's () Integrated school based nutrition programme improved the knowledge of mother and schoolchildren is a good example of an effectiveness evaluation. The authors report the implementation of an integrated school‐based nutrition programme that included gardening, nutrition education for parents, and supplementary feeding for children, and tested its impact on children's nutritional status.…”
Section: Summary Of Select Nutrition‐sensitive Cifsrf Projectsmentioning
confidence: 99%